Fibrous biocomposites from nettle (Girardinia diversifolia) and poly(lactic acid) fibers for automotive dashboard panel application. (1st December 2017) - Kumar, Navdeep; Das, Dipayan
Abstract: This work deals with fibrous biocomposites prepared by using nettle and poly(lactic acid) fibers and employing carding and compression-molding processes. The role of carding process in determining the tensile strength of the biocomposites was analyzed. The tensile, bending and impact properties of the biocomposites were found to increase initially with the increase of nettle fiber content till 50 wt% and decrease afterwards. The thermogravimetric analysis inferred that the thermal stability of the biocomposites increased with the increase of nettle fiber content. The dynamic mechanical analysis showed that the biocomposites exhibited high storage modulus, low loss modulus, and low damping factor. Further, the biocomposites exhibited excellent biodegradability and their biodegradability increased with the increase of nettle fiber content. Overall, the biocomposite prepared with equal weight proportion of nettle and poly(lactic acid) showed high potential for automotive dashboard panel application.